Looking at local government resilience through network data envelopment analysis - Sonny N. Domingo; Arvie Joy A. Manejar (Philippine Institute for Development Studies (PIDS), 2020)
The study looked into the resilience of provincial governance in the Philippines to disaster risk using World Bank (WB) socio-economic resiliency estimates and cross-sectional data generated by the Department of Interior and Local Government (DILG) and the Philippine Statistics Authority (PSA) during the period 2012-2013. Treating provincial governments as decision making units (DMUs) with bureaucratic sub-units at the provincial and city/municipal levels, composite efficiency scores were generated using an integrated Data Envelopment Approach. A World Bank generated socio-economic resiliency scorecard at the provincial level provided comparative output references for the model. It was empirically shown that disaster risk reduction and management inputs at the provincial and sub-province levels greatly contribute to improving socio-economic capacity and decreasing asset risk. However, DMU efficiency scores varied across the different sub-regional domains. A majority of provincial subDMUs also got higher efficiency ratings compared to their municipal/community subDMU counterparts, implying the need to rebalance support and disaster resilience -related initiatives at the sub-provincial levels.
Keywords: 330; Disaster Risk Reduction and Management; Disaster Resiliency; Data Envelopment Analysis